Try saying you're alive! : Kazuki Tomokawa in his own words - Tomokawa, Kazuki; Joseph, Daniel (Blank Forms Editions, 2021)
"Tokyo in the 1970s was a magnet for young musicians, poets and painters. Among them was Kazuki Tomokawa, a prolific singer-songwriter from Japan's northern provinces, whose guttural vocals and incisive lyrics earned him the unofficial title of 'screaming philosopher.' The stories in this memoir---originally published in 2015 in Japan and now appearing as the first English translation of Tomokawa's writing---are told with a rambler's wit and wisdom, bringing together his memorable reflections on six decades of day labor, drinking, gambling, acting, singing and writing. Figures such as Kan Mikami, Nobuyoshi Araki and Shūji Terayama drift through this down-and-out vagabond's memoir, which observes the turbulence of postwar countercultures and the explosion of Tokyo's underground film and music scenes."--Book jacket
Keywords: Tomokawa, Kazuki, : 1950-; muusikot; laulaja-lauluntekijät; musiker; singer-songwriters; Japani; Japan